MICRONUTRIENTS COMPOSITION OF MILLING STREAMS OF TRADITIONAL WHEAT CULTIVARS FROM SERBIA - Živančev, Dragan; Buljovčić, Maja; Ninkov, Jordanja; Antić, Igor; Mikić, Sanja; Jaćimović, Simona; Jocković, Bojan (Food and Feed Research, 2023)
The deficiency of micronutrients in the human diet is widely recognised as a global problem. The objective of this study was to assess the content of two essential minerals, iron and zinc, in milling streams of old heritage wheat cultivars that have not been produced for more than a half-century to discover potential parent lines with high mineral content for breeding. Kernel size of seven Serbian old wheat cultivars was evaluated for ash content, thousand-grain weight and share of specific kernel fractions. Three cultivars, Crnozrna, Rumska Crvenka and Stara Banatka, were selected as the most appropriate for milling and further analysis of mineral content in the milling streams. The cultivars were milled in a laboratory mill to obtain six flour and two by-product streams. At the same time, iron and zinc content was determined on a graphite furnace atomic absorption spectrometer. After mixing all six flour streams obtained from each cultivar, three different flour types were obtained. The flour with the highest ash content was the "1100" type originating from cultivar Stara Banatka, characterized by the highest iron and zinc content (54.9 mg/kg d. b. and 5.407 mg/kg d. b., respectively). It was estimated that consumption of a daily average bread portion (166 g according to national statistical data) made from Stara Banatka flour could provide about 90% of the recommended daily intake for iron. Therefore, Stara Banatka may be a target cultivar for wheat breeders searching for high-iron parent wheat lines.